A modified AHP algorithm for network selection - Huang, Xin; Jules, Guiovanni; Saadat, Mozafar; Rakhodaei, Hamid (Cranfield University Press, 2013)
This paper addresses the concept of ranking networks to the multiple criteria of customers to find the best and alternative networks. The use of modified AHP algorithm has been shown to provide better network ranking for reasonable customer objectives than the traditional AHP method. Both the traditional method and the proposed method produced results subjective to the customer requirements. However, the proposed method is more intuitive to the customers through direct capture of their exact requirements rather than an interpretation of their requirements through pair-wise comparison alone. Also, the proposed method is less time-consuming and results are of higher quality.
Keywords: AHP; Manufacturer networks; Multiple Criteria Decision Making